Z zagadnień etymologii gwarowej – luskopy - Kucharzyk, Renata (Gwary Dziś, 2022)
The aim of the article is to establish the etymology of a subdialectal word luskopy ‘shoulder yoke for carrying buckets of water. Luskopy functions as an indivisible word but it probably originated from the German compositum. The noticeable parallelism between the names of yokes and harness parts suggests that the first segment of the analysed compound may come from the German Ross ‘horse’. The second part of the compound may be derived from the German Koppel meaning a ‘leather belt’ or a ‘yoke’, or Kappe ‘headgear’.